[(C C)Au(N N)]+ Complexes as a New Family of Anticancer Candidates: Synthesis, Characterization and Exploration of the Antiproliferative Properties. Issue 63 (5th October 2021) - Khodjoyan, Silva; Remadna, Edwyn; Dossmann, Héloïse; Lesage, Denis; Gontard, Geoffrey; Forté, Jérémy; Hoffmeister, Henrik; Basu, Uttara; Ott, Ingo; Spence, Philip; Waller, Zoë A. E.; Salmain, Michèle; et al.
Abstract: A library of eleven cationic gold(III) complexes of the general formula [(C C)Au(N N)] + when C C is either biphenyl or 4, 4'‐ditertbutyldiphenyl and N N is a bipyridine, phenanthroline or dipyridylamine derivative have been synthesized and characterized. Contrasting effects on the viability of the triple negative breast cancer cells MDA‐MB‐231 was observed from a preliminary screening. The antiproliferative activity of the seven most active complexes were further assayed on a larger panel of human cancer cells as well as on non‐cancerous cells for comparison. Two complexes stood out for being either highly active or highly selective. Eventually, reactivity studies with biologically meaningful amino acids, glutathione, higher order DNA structures and thioredoxin reductase (TrxR) revealed a markedly different behavior from that of the well‐known coordinatively isomeric [(C N C)Au(NHC)] + structure. This makes the [(C C)Au(N N)] + complexes a new class of organogold compounds with an original mode of action. Abstract : The reorganization of the coordination sphere of the [(C N C)AuL] + scaffold led to the establishment of the [(C C)Au(N N)] + family with a preserved redox stability but an enhanced reactivity toward biomolecules making it a new class of organogold anticancer agent.